Development of an Educational Management Model for Antimicrobial Stewardship among Medical Students - Olivia A Waworuntu; Herry Sumual; Mozes M. Wullur; Ruth Umbase (International Journal of Information Technology and Education, 2026)
Antimicrobial resistance is one of the most urgent public health challenges in contemporary medical practice. Medical education has a strategic role in preparing future physicians to use antimicrobials rationally; however, antimicrobial stewardship is often taught in a fragmented manner, with limited integration between theoretical pharmacology, clinical reasoning, simulation, and digital self-directed learning. This article presents the development, feasibility assessment, and effectiveness evaluation of an educational management model for antimicrobial stewardship among medical students. The study applied a research and development approach using the ADDIE framework, consisting of analysis, design, development, implementation, and evaluation, while program evaluation was strengthened through the CIPP logic of context, input, process, and product evaluation. Data were obtained through curriculum review, observation, expert validation, learning trials, pre-test and post-test assessment, clinical simulation observation, and student feedback. The findings show that the developed model integrates problem-based learning, simulation-based learning, project-based learning, OSCE-oriented assessment, and digital online self-directed learning. Expert validation indicated that the module was highly feasible in terms of content, language, technology, and implementation. Implementation involving 40 medical students showed improvement in mean knowledge scores from 64.75 before intervention to 87.75 after intervention, with a significant Wilcoxon test result and very large effect size. Students also demonstrated improved clinical decision-making in indication, antimicrobial selection, dosing, duration, culture interpretation, and professional attitude. The model provides a structured, adaptive, and sustainable educational management framework for strengthening rational antimicrobial use in medical education.